Analysis of Legal Protection Strategy by Sub-Directorate II of Property of the Criminal Investigation Unit of the Indonesian National Police against the Mafia of Forgery of Ownership Certificates - Nurizki, Andhika Raka; Adhari, Ade (International Journal of Science and Society, 2025)
The rampant practice of land document forgery has caused public unrest and disrupted legal certainty over land ownership. This study aims to analyze the legal protection strategies implemented by Subdirectorate II of Property, Criminal Investigation Agency of the Indonesian National Police in handling cases involving the mafia of land ownership certificate forgery. This research uses an empirical legal research method with a descriptive qualitative approach, utilizing data collection techniques such as in-depth interviews, documentation studies, and observation. The results of the study indicate that Subdirectorate II of Property within the Criminal Investigation Agency of the Indonesian National Police has implemented various effective strategies in addressing cases of ownership certificate forgery perpetrated by land mafias. These strategies include legal education for the public, preventive measures through cooperation with related institutions, law enforcement against perpetrators, utilization of digital technology and document forensics, capacity building for investigators, and collaboration with the Anti-Land Mafia Task Force. The implementation of these strategies has had a positive impact in raising public legal awareness, strengthening inter-agency coordination, and reducing the number of forgery cases that harm both the state and the public.